2019
DOI: 10.5796/electrochemistry.18-00080
|View full text |Cite
|
Sign up to set email alerts
|

Surface State Change of Lithium Metal Anode in Full Cell during Long Term Cycles

Abstract: In order to investigate the surface state change of the lithium metal anode during long term cycles, a laminate-type lithium metal rechargeable battery was fabricated from a lithium foil, a Li 4 Mn 5 O 12 electrode, a polyimide (PI) membrane having a three-dimensionally ordered macroporous structure (3DOM) and a 1 mol dm −3 LiPF 6 ethylene carbonate (EC) solution as an anode, a cathode, a separator and an electrolyte, respectively. After the charge/ discharge cycles, the chemical composition at the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Various chemical approaches have been studied to solve this drawback, including the used of mixed-electrolyte salts and -solvents and the addition of organic and inorganic additives. [21][22][23] According to the report by Ding et al, the formation of dendritic crystals can be suppressed by the addition of cations with lower standard reduction potentials than that of lithium ions, such as cesium and rubidium ions. 24 Togasaki et al reported that the cycle performance of lithium plating/stripping reaction was stabilized by the use of LiNO 3 as the electrolyte salt.…”
Section: Introductionmentioning
confidence: 99%
“…Various chemical approaches have been studied to solve this drawback, including the used of mixed-electrolyte salts and -solvents and the addition of organic and inorganic additives. [21][22][23] According to the report by Ding et al, the formation of dendritic crystals can be suppressed by the addition of cations with lower standard reduction potentials than that of lithium ions, such as cesium and rubidium ions. 24 Togasaki et al reported that the cycle performance of lithium plating/stripping reaction was stabilized by the use of LiNO 3 as the electrolyte salt.…”
Section: Introductionmentioning
confidence: 99%
“…Similar residues have been observed in previous studies, in which the residues were found to contain inactivated Li comprising both chemically formed Li compound and electrically insulated Li metal. 26,[29][30][31][44][45][46] Thus, the amount of the residues is considered to be the dominant factor in determining the Coulombic efficiency of the Li electrode. This result suggests that the efficiency is lower for EC/PC with a mixture of fibrous and cord-shaped residues and high for EC/PC+VC and EC/PC+ FEC without cord-shaped residues.…”
Section: Resultsmentioning
confidence: 99%
“…21 A number of factors, such as electrolyte composition, current collector, separator, confined pressure, and applied current, affect the cycle performance of Li metal electrodes. [22][23][24][25][26][27][28][29][30][31][32][33][34] Utilization of Li, which determines the practical capacity of the negative electrode, also exerts a significant influence on the cycle performance. 28,[35][36][37] We previously reported that the use of 30% Li severely degrades the cycle performance of the Li negative electrode, using LiFePO 4 as a stable counter electrode to evaluate the Li electrode.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of deposited/ dissolved lithium and the cycle performance of lithium metal negative electrodes are influenced by a number of factors, such as the electrolyte composition, applied current, current collector, separator, and confined pressure. [7][8][9][10] These factors also differ depending on whether a lithium/lithium symmetric cell or full-cell combined with a positive electrode material is used for evaluations. Although these factors have been investigated in detail, limited information is currently available on the effects of lithium utilization on the cycle performance of the cell.…”
Section: Introductionmentioning
confidence: 99%